2018
DOI: 10.4314/tjpr.v17i9.17
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B2 enhances development of puberty ovaries via regulation of essential elements and plasma endocrine hormones

Abstract: Purpose: To investigate the effect of vitamin B2 (VB2) on ovarian development during puberty. Methods: Four groups of domestic hens (Jinghong-1 strain, 12 hens/group) were housed under standard conditions and fed basal diet with or without graded doses of VB2 (10-40 mg/kg). At 10 weeks old, 9 hens were sacrificed from each group. Plasma levels of AST, ALT, steroid hormones and growth hormones were determined. In addition, some essential mineral elements in the ovarian tissue of the hens were assayed. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…Previous studies also reinforce our findings, like pregnancy interruption due to deficiency of riboflavin was reported by [57, 58], their strong antioxidant roles mediated by free radicals was witnessed by [59]. In previous studies it has been observed the involvement of VB2 in ovarian development [60], bioenergetics pathways, redox homeostasis, chromatin remodeling [61, 62], deoxyribonucleic acid (DNA) repair mechanisms [63] and cell growth, and apoptosis [64, 65] which is in agreement to our findings of upregulated VB2 expression. ROC-AUC value determined that riboflavin (pos_4) may act as a potential biomarker for oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies also reinforce our findings, like pregnancy interruption due to deficiency of riboflavin was reported by [57, 58], their strong antioxidant roles mediated by free radicals was witnessed by [59]. In previous studies it has been observed the involvement of VB2 in ovarian development [60], bioenergetics pathways, redox homeostasis, chromatin remodeling [61, 62], deoxyribonucleic acid (DNA) repair mechanisms [63] and cell growth, and apoptosis [64, 65] which is in agreement to our findings of upregulated VB2 expression. ROC-AUC value determined that riboflavin (pos_4) may act as a potential biomarker for oxidative stress.…”
Section: Discussionsupporting
confidence: 91%